How to Read Aboriginal Legal Texts From Upper Canada - Walters, Mark (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2003)
AbstractIn this article the author considers the interpretive problems that arise when trying to read legal texts produced by aboriginal communities in mid-nineteenth colonial Canada. Using a code of laws enacted by the Credit River Mississaugas in 1830 as an example, he explores how written aboriginal laws from this time period appear to deviate from today’s judicial notion of aboriginal law as ancient, oral and customary in nature. The author suggests that aboriginal legal texts from the mid-nineteenth century may be read in four competing ways, which he labels as legal-historical, indigenist, ethnohistorical, and legal-constitutional. The author concludes that each of these methods of interpretation may offer valid insights into the role of law within aboriginal communities historically and today.